Pemberdayaan Keluarga Berbasis Budaya Minahasa dengan Deteksi Dini Hipertensi dan Kualitas Hidup Lansia - Meigi Rompas; Adriana Yuliana Mamesah; Yanny Joubert Lontoh (JURNAL ILMIAH KESEHATAN MANADO, 2026)
This study aimed to determine the relationship between Minahasa culture-based family empowerment and the early detection of hypertension and the quality of life of the elderly in Tember Village, Tompaso District. This study employed a quantitative method with a correlational design using a cross-sectional approach. The research sample consisted of 59 elderly respondents and their families selected using a purposive sampling technique. Results: The study showed a significant relationship between Minahasa culture-based family empowerment and the early detection of hypertension, with a -value of () and a weak negative correlation strength (). Conversely, there was no significant relationship between Minahasa culture-based family empowerment and the quality of life of the elderly, with a -value of (, ). Conclusion: Minahasa culture-based family empowerment is effective in supporting early detection capacity and controlling the severity of hypertension in the elderly, but does not directly correlate with the multidimensional quality of life of the elderly.